2016
DOI: 10.4236/cm.2016.74013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study of “Lingqi Huangban Granule” in Treating Choroidal Neovascularisation in Pathologic Myopia

Abstract: Objectives: To study the therapeutic effects of "Lingqi Huangban Granule" (LQHB) combined with intravitreal ranibizumab injection (IVR) for choroidal neovascularisation (CNV) in pathologic myopia (PM). Methods: This was a prospective, comparative, interventional study. Eighty eyes of eighty consecutive patients with myopic CNV were randomized into control group (IVR, 40 eyes) and integrative therapy group (IVR + LQHB, 40 eyes), each with a follow-up period of 12 months. IVR was given with an "on demand" regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…LQHBG, a famous traditional Chinese medicine formula that is used to manage retinal diseases, such as AMD, CRAO, CRVO, BRAO, and BRVO (Li et al, 2012, Gong et al, 2008, consisting of 10 crude herbs: Cistanche( RouCongRong), Lyciumbarbaruml(GouQiZi), Semen Cuscutae(TuSiZi), Codonopsispilosula(DangShen), Ganoderma(LingZhi), Rhizomaatractylodis(CangZhu), Salvia miltiorrhiza(DanShen), Angelica aculeolata(DangGui), Ligusticumwallichii(ChuanXiong), Sargassum(HaiZao) in a 3:2:2:2:2:2:2:2:2:2:2 ratio, which was developed by the First People's Hospital a liated with Shanghai Jiaotong University(Shanghai medicine system word: Z05050795). XingWei Wu et al suggested that LQHBG in combination with intravitreal ranibizumab injection effectively stabilizes and improves vision with fewer intravitreal injections, which may be an interesting option in this type of patients (Lu et al, 2016). Yuanyuan Gong et al also indicated that LQHBG protects retinal function and morphology from light-induced retinal damage in rats (Gong et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…LQHBG, a famous traditional Chinese medicine formula that is used to manage retinal diseases, such as AMD, CRAO, CRVO, BRAO, and BRVO (Li et al, 2012, Gong et al, 2008, consisting of 10 crude herbs: Cistanche( RouCongRong), Lyciumbarbaruml(GouQiZi), Semen Cuscutae(TuSiZi), Codonopsispilosula(DangShen), Ganoderma(LingZhi), Rhizomaatractylodis(CangZhu), Salvia miltiorrhiza(DanShen), Angelica aculeolata(DangGui), Ligusticumwallichii(ChuanXiong), Sargassum(HaiZao) in a 3:2:2:2:2:2:2:2:2:2:2 ratio, which was developed by the First People's Hospital a liated with Shanghai Jiaotong University(Shanghai medicine system word: Z05050795). XingWei Wu et al suggested that LQHBG in combination with intravitreal ranibizumab injection effectively stabilizes and improves vision with fewer intravitreal injections, which may be an interesting option in this type of patients (Lu et al, 2016). Yuanyuan Gong et al also indicated that LQHBG protects retinal function and morphology from light-induced retinal damage in rats (Gong et al, 2008).…”
Section: Introductionmentioning
confidence: 99%